Project Report on Design and Implementation of Software Simulation Aircraft Flight Controls and Monitoring - RAKESH VYAS, RAHUL MISHRA, UDAY KIRAN and AMIT PRASAD (2009)
INTERNAL GUIDE:V KESAVAN, MVJCE EXTERNAL GUIDE:M S PATEL, SOFTWARE DEVELOPER INTAGLIO SYSTEM PVTLTD
Keywords: Flight Controls and Monitoring